2006
DOI: 10.1029/2005jd006143
|View full text |Cite
|
Sign up to set email alerts
|

Secondary particle formation and evidence of heterogeneous chemistry during a wood smoke episode in Texas

Abstract: [1] To evaluate the impact of regional wildfires in east Texas on fine particulate matter concentration and composition, source apportionment calculations were performed on a set of samples collected at three sites in Houston during a wood smoke episode. Separately, samples collected at the same sites on days not influenced by wood smoke, were analyzed for comparison. The analysis of the data collected on non-wood smoke episode days indicated that the major contributors to PM 2.5 mass were secondary sulfate, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Buzcu et al 33 and Nopmongcol and Allen 35 also report very high sulfate concentrations during the fire episode that occurred during the Supersite intensive measurement period and concluded that the fire particles were catalyzing the formation of additional sulfate. Data emerging from other field programs support the hypothesis that fire particles catalyze soot formation.…”
Section: Texas Gulf Coastmentioning
confidence: 99%
See 2 more Smart Citations
“…Buzcu et al 33 and Nopmongcol and Allen 35 also report very high sulfate concentrations during the fire episode that occurred during the Supersite intensive measurement period and concluded that the fire particles were catalyzing the formation of additional sulfate. Data emerging from other field programs support the hypothesis that fire particles catalyze soot formation.…”
Section: Texas Gulf Coastmentioning
confidence: 99%
“…Wood smoke was found to be highly episodic as a source, and the strength of the source was most dependent on fires occurring within a several-hundred-kilometer radius of Houston. Junquera et al 34 estimated emissions from the fires during the Supersite intensive measurement period considered by Buzcu et al 33 and found that, during periods of intense fire activity, fires can become the dominant primary source of PM 2.5 in the region.…”
Section: Texas Gulf Coastmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, CMB and PMF approaches were used to estimate the source contributions to PM 2.5 levels with an organic marker compound and it was found that the impact of direct emissions from biomass combustion can be isolated from the effects of primary emissions on secondary sulfate formation. 213 The application of PMF to the source apportionment of carbonaceous material in the atmosphere will be examined using the results from four recent studies. These studies have different objectives and, hence, different protocols and outcomes.…”
Section: Pmf Modelmentioning
confidence: 99%
“…Estimates based on measurements of levoglucosan (a molecular marker of wood smoke) and on estimates of fire acreage and land cover burned are consistent in indicating that wildfires and controlled burns of biomass contribute of order 1-2% of the annual average total PM 2.5 mass in the Houston-Galveston area. 75,77,116 • Geological sources of PM 2.5 (dust) are a relatively minor contributor to total PM 2.5 mass in the urban Houston-Galveston, TX, area. Buzcu et al 116 and Yue and Fraser 117 have estimated that road dust accounted for an average of 0.3 g/m 3 of PM 2.5 mass (2% of total PM 2.5 mass) in August and September 2000, at a ship channel area site (Houston Regional Monitoring Site No.…”
Section: Houston Txmentioning
confidence: 99%